(untitled) (Journal of the College of Basic Education, 2022)
This study aims to identify the narrative structure in the poetry of (Tamim bin Moqbel), and to highlight the impact of this structure on his poetry, which achieved a high degree of artistic depth, and contributed to the service of the poetic experience. It also aims to shed light on the poet and his directions in the folds of the poetic text. who became a narrator and a poet at the same time. The poet used (time, characters, and event) to express his views and attitudes towards the universe, and his reality in light of the radical changes in Arab life that accompanied the emergence of Islam as a veteran poet who lived in this transitional period and realized its variables. If we chose the title (Features of Narrative Construction in Tamim bin Muqbil’s Poetry), time had a clear presence, and during this time the poet tried to return to the past in most of his poems; To take back the time he was proud of.This study is an attempt to illuminate the narrative structure in the poetry of (Tamim bin Muqbil), and to reveal the features of the influence that enriched the poetic texts, and the aesthetic and artistic advantages that this structure added.